2012
DOI: 10.1016/j.bpj.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Coupling of Protonation and Conformational Equilibria in Proteins: Theory and Simulation

Abstract: Ionization-coupled conformational phenomena are ubiquitous in biology. However, quantitative characterization of the underlying thermodynamic cycle comprised of protonation and conformational equilibria has remained an elusive goal. Here we use theory and continuous constant pH molecular dynamics (CpHMD) simulations to provide a thermodynamic description for the coupling of proton titration and conformational exchange between two distinct states of a protein. CpHMD simulations with a hybrid-solvent scheme and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
78
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 32 publications
(42 reference statements)
5
78
0
1
Order By: Relevance
“…31,32 The hybrid-solvent data shows a slope well below one (0.61), indicative of a systematic underestimation of p K a shifts, which is due to the underestimation of desolvation penalty by the GBSW model (”too wet”). 8,9,57 The above-mentioned trend can also be seen from the histogram of p K a deviations, p K a calc - p K a expt (Fig. S6).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…31,32 The hybrid-solvent data shows a slope well below one (0.61), indicative of a systematic underestimation of p K a shifts, which is due to the underestimation of desolvation penalty by the GBSW model (”too wet”). 8,9,57 The above-mentioned trend can also be seen from the histogram of p K a deviations, p K a calc - p K a expt (Fig. S6).…”
Section: Resultssupporting
confidence: 56%
“…Such overshifts are not seen in the hybrid-solvent simulations, which may be in part attributed to the fortuitous cancellation of errors between the underestimation of desolvation by the GBSW model and the overestimation of desolvation resulting from inadequate structural relaxation based on our previous studies of buried residues. 9,57 …”
Section: Resultsmentioning
confidence: 99%
“…The most widely employed approach regarding these models is the Constant pH Molecular Dynamics (CpHMD) (Bürgi et al, 2002 andMongan et al, 2004), in which the solution pH should be specified as an external variable. One advantage of these CpHMD methods is that they allow the investigation of pH-dependent properties of proteins, and the correlation between protonation and conformational states (Dissanayake et al, 2015;Shi et al, 2012 andZeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…26 Combined with the pH replica-exchange sampling protocol, 26 it offers accurate p K a convergence on the order of 1 ns per pH replica, 26 in particular for interior sites of proteins that are notoriously challenging to predict with static structure-based electrostatics methods. 27,28 A benchmark study showed that hybrid-solvent CpHMD can predict the p K a ’s of enzyme catalytic sites with a correct order and accuracy of about 1 pH unit. 26 Most recently, we applied hybrid-solvent CpHMD to study the apo form of BACE1, revealing a pH-dependent population shift between three conformational states that gives rise to the bell-shaped pH profile of the enzymatic activity.…”
mentioning
confidence: 99%